Agriculture in Eastern European countries: Light at the end of the tunnel? - Eckart Guth (Intereconomics, 1990)
Following recent events in East European countries the question has arisen as to what effect the possible changes in the agricultural policies of these countries might have on agricultural production and trade. Our author addresses this question paying special regard to the consequences for EC agriculture and the present GATT Round.
Keywords: 330; East-West Relations